PANEL RESPONSE: FINANCIAL SECTOR POLICY - Reflections on the Irish Banking Crisis - Whelan, Karl (The Economic and Social Review, 2025)
The titans of global banking often like to portray themselves as buccaneering free market entrepreneurs, but the reality is that banking systems everywhere are deeply intertwined with government. While the role that banks play as financial intermediaries is crucial for both savers and borrowers, the combination of fraction reserve banking with maturity mismatch means that, left to itself the banking system is innately unstable. To keep the show on the road, government-provided backstops such as deposit insurance and a lender of last resort function are required. Governments also need to regulate and supervise the banking sector very carefully because bankers largely prioritise short-term profitability over long-term stability – most banking crises are not accidents but require a combination of bad supervision by governments and bad behaviour by bankers. More than any other European economist, Patrick Honohan has unique experience both in witnessing how banking systems can collapse and in putting various banking sector Humpty Dumpties back together again.